2018
DOI: 10.3390/cli6020048
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Drought Forecasting for Latin America Using the ECMWF S4 Forecast System

Abstract: Meaningful seasonal prediction of drought conditions is key information for end-users and water managers, particularly in Latin America where crop and livestock production are key for many regional economies. However, there are still not many studies of the feasibility of such a forecasts at continental level in the region. In this study, precipitation predictions from the European Centre for Medium Range Weather (ECMWF) seasonal forecast system S4 are combined with observed precipitation data to generate fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…In East, Central, West, North and Southern Africa up to 44% (ECMWF), 46% (UK‐Met), 58% (CMCC), 47% (UK‐Met), 39% (Meteo‐France), and 38% (UK‐Met) of droughts events are forecasted by the models, respectively. Similar to our findings, in Latin America, ECMWF showed a POD of 30% for drought events with FAR less than 70% (Carrão et al., 2018). The drought forecast performance is improved when using the MMM and WMMM.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…In East, Central, West, North and Southern Africa up to 44% (ECMWF), 46% (UK‐Met), 58% (CMCC), 47% (UK‐Met), 39% (Meteo‐France), and 38% (UK‐Met) of droughts events are forecasted by the models, respectively. Similar to our findings, in Latin America, ECMWF showed a POD of 30% for drought events with FAR less than 70% (Carrão et al., 2018). The drought forecast performance is improved when using the MMM and WMMM.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…In September, the opposite occurs, and SEAS5 low-precipitation forecasts are much worse than its predictions of normal precipitation variability (Figures 2 and 4). The overall seasonal variability aligns with findings from other studies of the previous version (S4); Carrão et al (2018), for instance, demonstrated relatively lower skill in May and June relative to July and August across much of Central America when measuring S4 skill for predicting SPI at 3-month lead time.…”
Section: Seasonal and Lead Time Variability In Seas5 Skillsupporting
confidence: 85%
“…Dynamic forecasting systems like SEAS5 require more localized evaluation in the CADC specifically, as relatively few evaluations have focused on how these systems perform across the region, and their quality may vary regionally. Some studies have addressed how the previous version of the ECMWF forecasting system (S4) performed over Central America more generally (e.g., Dutra et al ., 2014; Weisheimer and Palmer, 2014; Carrão et al ., 2018), and others have investigated SEAS5 performance in nearby regions (e.g., in South America; Gubler et al ., 2020). For instance, Weisheimer and Palmer (2014) showed S4 had a perfect reliability score in predicting precipitation variability over Central America during June through August (JJA) and December through February (DJF) using initialization periods of 2 and 4 months in both relatively warm and cool years.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth highlighting the improvement of the new ECMWF seasonal forecast system (SEAS5) compared with the older version (S4). Indeed, the patterns found over South America look relatively similar to those obtained in (Carrão et al 2018), but with a clear increase of significance. The same scores as those used by these authors reveal this improvement between the two versions (not shown).…”
Section: B Evaluation Of Warning Levels For Forecasted Unusually Wetsupporting
confidence: 73%